Hybrid photodiodes based on 6,13-bis(triisopropylsilylethynyl) pentacene: poly[2-methoxy-5-(2-ethyl) hexoxy-phenylenevinylene]/p-silicon - Alahmed, Z. A.; Mansour, Sh A.; Aydin, M. Enver; Yakuphanoğlu, Fahrettin (Pergamon-Elsevier Science Ltd, 2013)
6,13-Bis(triisopropylsilylethynyl) pentacene (TIPS) and poly[2-methoxy-5-(2-ethyl) hexoxy-phenylenevinylene] (MEH-PPV) blends with different ratios were deposited onto a p-type silicon (p-Si) single crystal wafer using spin coating technique. The dark current-voltage characteristics of the fabricated diodes were studied at room temperature. This study was carried out to predict the best blend composite to obtain a qualified diode for use in potential application. The obtained results suggest that the diode with 10:4 ratio between TIPS and MEH-PPV has the highest values for both the rectification factor (r=1.7 x 10(3)) and the ratio between shunt resistance, R-sh, and series resistance, R-s, (R-sh/R-s=1.23 x 10(4)) among the investigated diodes. Accordingly, the capacitance-voltage-frequency and conductance-voltage-frequency measurements were carried out for this diode in the frequency range between 10 kHz and 1 MHz at room temperature. Moreover, the I-V characteristics of such a diode were studied under different illumination intensities (P = 20 : 100 mW/cm(2)). The obtained results show a highly optoelectric response; i.e., the diode can be operated as a heterojunction photodiode. Crown Copyright (c) 2013 Published by Elsevier Ltd. All rights reserved.
Keywords: 6,13-Bis(triisopropylsilylethynyl) pentacene; Poly[2-methoxy-5-(2-ethyl) hexoxy-phenylenevinylene]; Diode parameters; Photodiode